Exploring iodized salt consumption and storage practices in urban slums of Bhubaneswar: a cross-sectional analysis - Suresh, Snehapriya; Giri, Prajna Paramita; Behera, Binod Kumar; Subba, Sonu H. (International Journal Of Community Medicine And Public Health, 2025)
Background: Salt iodization is the most effective public health intervention to prevent iodine deficiency disorders. This study aimed to estimate the proportion of households using adequately iodized salt at the consumer level and assess knowledge and practices regarding iodized salt usage and storage. The study also assessed the association between salt storage practices, awareness about iodized salt, and iodine levels in salt. Methods: A cross-sectional study was conducted in the urban slums of Bhubaneswar from May to July 2022. The required sample size was calculated to be 95 households, selected through systematic random sampling proportionate to the size of each ward. The multibus interface (MBI) kit was used for spot testing of iodine. Data analysis was performed using SPSS version 26.0. Results: The proportion of households using adequately iodized salt was 91.6%. About 13.7% stored salt in open containers, 65% near the fire/gas, 21.1% stored salt for more than four weeks, and 7.4% had moisture in their salt. About 53% of households added salt in the beginning of cooking and 81% of respondents had poor knowledge about iodized salt. Storing salt in open containers or sacks was significantly associated with inadequate iodine levels in salt (p value: 0.01). Conclusions: While the consumption of adequately iodized salt meets the target level of 90%, poor awareness and improper storage practices are still prevalent. Education on proper storage, handling, and the importance of iodized salt is crucial to increase community awareness and improve iodine levels in salt.